EDUCAÇÃO DOMICILIAR: A TENSÃO CONSTITUCIONAL ENTRE A LIBERDADE DE ENSINO E O DEVER DE PROTEÇÃO - Vanzella Correia, Laura; Carine Palma Mattiello, Darléa (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2025)
This study, titled "EDUCAÇÃO DOMICILIAR: A TENSÃO CONSTITUCIONAL ENTRE A LIBERDADE DE ENSINO E O DEVER DE PROTEÇÃO," analyzes the legal and social debate surrounding homeschooling in Brazil. The absence of a federal legal framework for the practice has created a legislative vacuum, raising questions about its compatibility with the right to education. The research aims to clarify the legal possibilities and limitations for implementing homeschooling, balancing the freedom of family choice with the state's duty to ensure a child's full development. The analysis was conducted using a qualitative, hypothetico-deductive approach, drawing from legal texts, legislative opinions, judicial rulings, and academic articles. The study revealed a landscape of intense discussion and limited regulation, despite over 35,000 families adopting the practice as of 2021. The Supreme Federal Court (STF) ruled that homeschooling is constitutional but requires legal regulation. While some municipalities and states, such as Chapecó, have attempted to regulate it, their laws have been declared unconstitutional due to formal issues. The Ministry of Education (MEC) has expressed a favorable position toward federal regulation, provided there is a virtual registration platform and annual student evaluations. The study concludes that the main legal challenge of homeschooling is not its admissibility but finding a legal model that can meet the growing social demand. The findings suggest that overcoming the current legal vacuum requires creating a federal law. This law should harmonize the competing rights and establish clear oversight mechanisms to ensure the full development of children and adolescents without infringing on family autonomy.